Fundamentals of Entrepreneurship (ENT300) : Rebel selling clothes and apparel / Ahmad Shadiqin Ali Rahman ... [et al.] - Ali Rahman, Ahmad Shadiqin; Tony, Muhammad Dzikry; Abg Zolfaka, Dyg Nur Zinnirah; Sabarin, Nur Izzah
For business opportunity, we had chosen clothes as our selling item for our business. It was observed that shops that sell clothes are either far away from the consumer’s area, the clothes are low in quality, the shop sells the clothes at an unreasonable price, or all of them combined. Our business will be located at The Hub in Matang area. We had chosen this location due to its strategic location, which is near to housing areas, thus has a strong potential to attract customers. And the time of operation would be from 10am to 10 pm.